The Role of Audio Visual Media in Improving Students’ Listening Comprehension - Ramadhan, Syahril; Azralia, Chelsi; Habibi, Irfan; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Listening comprehension is a key component of language proficiency and plays a vital role in academic and everyday communication. However, many students struggle with this skill due to a lack of exposure to authentic language input and engaging materials. The integration of audio-visual (AV) media into language instruction has gained popularity as an effective means to support listening comprehension. This article explores the role of AV media in improving students' listening comprehension based on a review of 25 SINTA-accredited journal articles from the last five years. It discusses theoretical frameworks, types of AV media, pedagogical benefits, implementation strategies, challenges, and practical implications for language teaching.